Inclusión de acacia (Acacia Mearnsii) en dietas y efecto en la función ruminal y producción de CH4 y CO2 - Varas Aguillón, Jefferson Raúl (2020)
The effect of the inclusion of Acacia mearnsii in bovine diets in a completely randomized design was evaluated using four treatments and six repetitions with different levels of inclusion of A. mearnsii (T1: Medicago sativa 50%, Lolium perennial 50%; T2: Medicago sativa 40%, Lolium perennial 40%, Acacia mearnsii 20%; T3: Medicago sativa 30%, Lolium perennial 30%, Acacia mearnsii 40% and T4: Medicago sativa 20%, Lolium perennial 20%, Acacia mearnsii 60%) it was used six two-year-old cannulated mestizo bulls with an average weight of 350 kilos. Degradability test of the MS and MO was performed using the nylon bag technique and in vitro digestibility. Digestibility was higher (P <0.0001) in treatments 1 and 2, ruminal degradability in the soluble fraction (a), degradation potential (a + b) and effective degradation was greater (P <0.05) in T1, the fraction insoluble but potentially degradable (b) and the degradation rate in% per hour (c) showed no differences between the evaluated treatments (P> 0.05), the ruminal pH, there were no differences (P> 0.05) between treatments, the production of Methane gas was lower in T2 with a difference of 48.4 mL methane / 0.500mg of Fermentable MS compared to T4. The lowest production of carbon dioxide was observed in treatments T1 and T2 (P <0.0063) with a difference of 236 mL CO2 / 0.500mg of Fermentable MS compared to T4. It is concluded that the inclusion of A. mearnsii positively influences ruminal function and reduces the production of rumen gases.